War and organizational disruption in professional service firms. Issue 3 (12th July 2018) - Walker, Stephen P
ABSTRACT: This article presents the results of an historical study of disruption in professional service firms. The focal disturbance was the labour depletion crisis that arose from the mass enlistment of staff for military and government service during the First World War. The study draws on the surviving archives of military service tribunals, government papers, the records of professional organizations, and contemporary periodicals to perform a micro analysis of disruption in chartered accountancy practices in Edinburgh. The linked concepts of vulnerability, adaptability, and resilience are deployed to explore the impacts of the perturbation. The article identifies the features that rendered accountancy firms more or less susceptible to the harm wrought by the depletion crisis; explores the adaptive activities pursued by practitioners and professional bodies to moderate the impacts of trauma; and reveals how accounting firms absorbed the disturbance and successfully preserved their institutional structures and ideologies.